2013
DOI: 10.1056/nejmoa1212722
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Trial of Glutamine and Antioxidants in Critically Ill Patients

Abstract: Early provision of glutamine or antioxidants did not improve clinical outcomes, and glutamine was associated with an increase in mortality among critically ill patients with multiorgan failure. (Funded by the Canadian Institutes of Health Research; ClinicalTrials.gov number, NCT00133978.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
442
4
54

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 793 publications
(517 citation statements)
references
References 19 publications
17
442
4
54
Order By: Relevance
“…In principle, the same eff ect applies in critically ill pediatric patients, but here the low mortality rates have not made it possible to demonstrate a mortality disadvantage, although a morbidity disadvantage has been reported [6]. Approximately one third of ICU admissions are consistently found to have a low plasma glutamine concentration, and this is independent from conventional risk-scoring [1], [4]- [6]. In a study from Stockholm, the mortality associated with a low ICU admission glutamine concentration was to a large extent due to the post-ICU mortality within 6 months from ICU admission [5].…”
Section: Rationale For Supplementationmentioning
confidence: 93%
See 2 more Smart Citations
“…In principle, the same eff ect applies in critically ill pediatric patients, but here the low mortality rates have not made it possible to demonstrate a mortality disadvantage, although a morbidity disadvantage has been reported [6]. Approximately one third of ICU admissions are consistently found to have a low plasma glutamine concentration, and this is independent from conventional risk-scoring [1], [4]- [6]. In a study from Stockholm, the mortality associated with a low ICU admission glutamine concentration was to a large extent due to the post-ICU mortality within 6 months from ICU admission [5].…”
Section: Rationale For Supplementationmentioning
confidence: 93%
“…Th e study has been criticized for the relatively low dose of glutamine given, for not communicating how much of the intended dose the patients were actually given, and for the limited time period of treatment. Th e REDOXS study, on the other hand, was not neutral in terms of outcome, rather it demonstrated harm [1]. It is the fi rst study to demonstrate harm related to provision of exogenous glutamine in critically ill patients.…”
Section: Comments On Recent Studies With Glutamine Supplementationmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients who were diagnosed with MOF within 24 h from ICU admission were eligible for the study. The definition of MOF referred to criteria in a previous study, which included patients with MOF caused by various diseases 8. Further details of definitions are as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple organ failure was defined as the presence of two or more organ failures related to their acute illness. Organ failures were defined as: (i) respiratory failure, mechanically ventilated and a PaO 2 /FiO 2 ratio of <300; (ii) hypoperfusion, to maintain circulation, vasopressor agents (norepinephrine, epinephrine, vasopressin, or >5 μg/kg/min dopamine) required for 2 h or longer; (iii) renal dysfunction, in patients without known chronic kidney disease, serum creatinine >1.93 mg/dL, or a urine output of <500 mL/last 24 h (or 80 mL/last 4 h if a 24‐h period of observation not available), in patients with acute on chronic renal failure (predialysis), an absolute increase of >0.90 mg/dL from baseline creatinine, or a urine output of <500 mL/last 24 h (or 80 mL/last 4 h); and (iv) thrombocytopenia, platelet count of ≤50 × 10 9 /L 8. We excluded patients who met any of these criteria: (i) younger than 18 years; (ii) admitted after elective cardiac surgery; (iii) died within 24 h of ICU admission; (iv) a history of organ transplantation; (v) readmission to ICU within 28 days; (vi) treated with ulinastatin before ICU admission; and (vii) treated within ulinastatin <3 days.…”
Section: Methodsmentioning
confidence: 99%